Tratamento de dejetos bovinos em sistema intensivo de produção de leite com aeração mecânica - Assenheimer, Adriane (2007)
This work had as objective to evaluate the acting of an aeration equipment adopted in the treatment of dejections of bovine confined in the system ?free stall?, with the recycling of the diluted effluent in the cleaning of the facilities and subsequent use in the areas of cultivation of forages. A reactor was used, operated by the process of mud activated by ?boat-load? (LAB), with system of lingering and intermittent aeration, dimensioned for a time of hydraulic retention of 24 days, with dilution of the dejections in water in the proportion of volume 1:1. Samplings were accomplished in the entrance and inside the aeration tanks, in the exit of the irrigation tubulation and of the pure dejections of the animals. The following parameters were determined: pH, temperature, total Biochemical Oxygen Demand (BOD), total Chemical Oxygen Demand (COD), organic matter, total solids, total fixed solids, total solids suspended, solids suspended fixed, solids suspended volatile, total nitrogen, nitrogen amoniacal, potassium, phosphorus, total carbon, calcium and magnesium. High reductions of BOD (59,05%) and COD (48,16%) were reached for the irrigation effluent. Related to the stabilization of the organic matter, the relationship C/N of the irrigation effluent was of 13,9, indicating that the effluent was stabilized. Through the obtained results, it was found that the aeration system was efficient to reduce and to stabilize the organic matter of the liquid effluent, making possible the recycling in the cleaning of the facilities, providing considerable economy of water, with subsequent release of that treated effluent in the cultivation areas, improving the physical, chemical and biological characteristics of the soil